Inequalities in large‐scale breastfeeding programmes in Bangladesh, Burkina Faso and Vietnam - Tina G. Sanghvi; Deepali Godha; Edward A. Frongillo (Wiley, 2024)
Abstract Inequalities in breastfeeding programmes and practices have slowed global progress in providing the life‐saving protection of breastfeeding for millions of infants despite well‐known life‐long impacts. As breastfeeding interventions are scaled up, inequalities in coverage and breastfeeding practices should be tracked, particularly in disadvantaged groups, who are likely to suffer the most serious health and developmental impacts of poor childhood nutrition. The literature provides evidence of inequalities in breastfeeding practices, but research is limited on socioeconomic disparities in the coverage of breastfeeding interventions. This paper (1) compares inequalities in breastfeeding practices in intervention and nonintervention areas and (2) documents inequalities in programme coverage by type of intervention. We disaggregated endline evaluation surveys in Bangladesh, Burkina Faso and Vietnam, where rigorous evaluations had documented significant overall improvements, and analysed whether inequalities in breastfeeding practices and programme coverage differed by treatment areas. We used Erreygers index to quantify inequalities and found that breastfeeding practices were largely pro‐poor; intervention coverage was not consistently pro‐poor. While counselling coverage often favoured women from the poorest quintile, public education/media coverage consistently favoured better‐off women. Inequalities favoured more educated mothers in the coverage of combined interventions. None of the programmes had explicit equality objectives. The results indicate the need for introducing specific actions to reduce inequalities in breastfeeding policies and programmes. This is a priority unfinished agenda for nutrition programming.